Seance [videorecording (DVD)] - Barrett, Simon; Barrett, Simon; Waterhouse, Suki, 1992-; Beaty, Madisen, 1995-; Smith, Ella-Rae, 1998- (Image Entertainment, 2021)
When a young woman arrives at the Fairfield Academy following one of the student's untimely and violent death, she joins a seance to try to connect with the deceased girl's spirit.